Germany’s International Career Services: Marketing Mismatches and Sustainable Structures - Schueller, Jessica (International Higher Education, 2022)
Retaining international students is central to many countries’ economic development policies. One manifestation of these efforts is the development of international student career services, which are established to support international students in pursuing careers in the host country. Examples of international student career integration in the Anglosphere are abundant. This article examines the German context, offering perspectives to non-Anglophone countries interested in sustainably attracting, recruiting, supporting, and retaining international talent.